THE EFFECTIVENESS OF FANTASY STORIES TECHNIQUE TOWARDS STUDENTS’ CREATIVITY IN WRITING - Supriadi, Ujang (JOLLT Journal of Languages and Language Teaching, 2018)
This research is aimed to find out whether or not using Fantasy Stories TechniqueÂ Toward Studentsâ€™ Creativity in Writing is effective. The research was experimental research and the design used was used one group pre-testÂ post-test design. The population of the study was the second grade students of SMA Negeri 1 Praya Timur which consisted of only one class with 25 studentsâ€™. So, the researcher took all the number of population as the sample. The data were collected by using pre-test and post-test. The instrument of this research used was writing test. The technique that was used to analyse the data was t-test formula. From the data analysis, it was found that the result of t-test (2,296) was higher than t-table (1,711) at the significant level = 0,05 and the number of degree of freedom (df) = 24. Therefore. Based on the result of the analysis. It can be concluded that Fantasy Stories TechniqueÂ Towards Studentsâ€™ Creativity in Writing at the Second Grade Studentsâ€™ofÂ SMAN 1 Praya Timur in academic year 2017/ 2018 is effective.